The Concept of Memory in the Work of Miroslav Volf: A Critical Survey = Koncepcija pam’jati u pracjach Myroslava Volʹfa: krytyčnyj ohljad - Matsyuk, Vasyl (Bogoslovs'ki rozdymi, 2025)
Miroslav Volf’s concept of memory is deeply connected to his broader theological vision, shaped by his understanding of grace, reconciliation, and eschatological hope. This article surveys how memory fits within Volf’s Christian framework, particularly its relationship to atonement and divine generosity. In The End of Memory, he argues that while memory is essential for justice and identity, it must ultimately be transformed by grace. In the eschaton, the memory of wrongdoing will gradually fade as a gift from God, making perfect communion with God and one another possible. This study explores how Volf’s eschatology informs this claim and considers whether his framework sufficiently accounts for the moral weight of past suffering and the need for recognition. Engaging with critiques of his position, the article examines how his reflections on forgiveness, justice, and reconciliation shape his approach to remembering rightly. By situating his concept of memory within his larger theological project, this survey provides an overview of its role in his vision of redemption and the world to come.